Tingkat Kerapatan Mangrove dan Perubahan Garis Pantai Tahun 2016-2022 Menggunakan Citra Satelit Sentinel-2A di Kecamatan Bungus Teluk Kabung - Kurniawan, Rizky; Triyatno, Triyatno (Lembaga Yasin AlSys, 2024)
This study aims to, (1) Know the distribution and extent of mangrove land in Bungus Teluk Kabung District, (2) Know the density of mangroves in Bungus Teluk Kabung District, (3) Know the changes in coastline in Bungus Teluk Kabung District, (4) Know the relationship between mangrove density with changes in coastline in Bungus Teluk Kabung District. The research method used is descriptive quantitative, with data presented in the form of tables and maps. Based on the results of the study, (1) Changes in mangrove land area in 2016-2022 amounted to 84.04 ha to 94.39 ha spread in the sub-district of Teluk Kabung Tengah and Teluk Kabung Selatan. (2) The level of mangrove density in 2016 and 2022 is equally dominated by the density level of tight and then followed by the level of very tight, moderate, sparse and very sparse, where the tight level in 2016 is 81.57 ha in 2022 is 80.78 ha. (3) Shoreline changes in 2016-2022 are divided into 5 sectors. (4) The presence of mangroves does not significantly affect the occurrence of shoreline changes in the form of abrasion.